Feasibility of resonant diffraction radiation from inclined gratings for a nondestructive beam diagnostics; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Potylitsyn A. P. Alexander Petrovich; Mkrtchan A. R. Alpik Rafaelovich; Kocharian V. R. Vagan Rashidovich; Novokshonov A. I. (Physical methods in science and engineering, 2015)
Title screen